The nucleotide sequence of the cloned nusA gene and its flanking region of Escherichia coli. - Ishii, S (1984)
The nucleotide sequence of the promoter-proximal portion of the nusA operon including the genes for tRNAMetf2, a 15 kilodalton protein and the initial portion of the nusA gene has been determined previously (1). Here, we report the sequence for the entire nusA gene and its flanking region. The open reading frame, consisting of 1,482 nucleotides, was identified as that of the nusA protein on the basis of agreement of the amino acid sequence deduced from the DNA sequence with the N-terminal sequence of the purified nusA protein. The molecular weight of 54,417 daltons calculated for the 494 amino acid polypeptide is significantly lower than that determined previously by SDS polyacrylamide gel analysis. The nusA gene is immediately followed by another open reading frame encoding a polypeptide of at least 22 amino acids, which was identified as the initial portion of the infB structural gene. In the spacer region of 24 base pairs between the nusA and infB structural genes there is no significant DNA sequence that fits the canonical transcriptional termination signal or promoter sequence. We suggest, therefore, that the genes for tRNAMetf2, a 15 kilodalton protein, the nusA protein and IF2 alpha, aligned in this order, are co-transcribed.